ILU-12 commissioning - Auslender, V.L.; Bryazgin, A.A.; Chernov, K.N.; Cheskidov, V.G.; Factorovich, B.L.; Gorbunov, V.A.; Gornakov, I.V.; Korobejnikov, M.V.; Kuznetsov, G.I.; Makarov, I.G.; Matyash, N.V.; Ostreiko, G.N.; et al. (Вопросы атомной науки и техники, 2008)
At Budker INP SB RAS, a prototype of high-power industrial electron accelerator for the energy of 5 MeV,
named ILU-12, has been successfully commissioned. The accelerator operates at 176 MHz. The paper presents the
accelerator concept together with simulation results for the accelerating structure, beam injection and dynamics.
The obtained beam pulsed power of 1,5 MW at the structure electron efficiency of 67% is close to the simulation
value. Improvements of beam transportation and energy spectrum due to the injection regime optimization were
experimentally proven. The results obtained are discussed. В ІЯФ СВ РАН зроблено успішний запуск прототипу потужного промислового прискорювача електронів
ІЛУ-12 на енергію 5 МеВ. Робоча частота прискорювача 176 МГц. Коротко описується концепція прискорювача. Приводяться результати розрахунків прискорювальної структури, інжекції і динаміки пучка. Отримано близькі до розрахункових імпульсна потужність пучка (1,5 МВт) і електронний ККД прискорювальної структури (67%). Експериментально підтверджено поліпшення проходження пучка і його енергетичного спектра за допомогою оптимізації режиму інжекції. Обговорюються отримані результати. В ИЯФ СО РАН произведен успешный запуск прототипа мощного промышленного ускорителя электронов ИЛУ-12 на энергию 5 МэВ. Рабочая частота ускорителя 176 МГц. В докладе кратко описывается концепция ускорителя. Приводятся результаты расчетов ускоряющей структуры, инжекции и динамики пучка. Получены близкие к расчетным импульсная мощность пучка (1,5 МВт) и электронный КПД ускоряющей структуры (67%). Экспериментально подтверждено улучшение прохождения пучка и его энергетического спектра с помощью оптимизации режима инжекции. Обсуждаются полученные результаты.